A novel 17β-hydroxysteroid dehydrogenase in Rhodococcus sp. P14 for transforming 17β-estradiol to estrone. (1st October 2017) - Ye, Xueying; Wang, Hui; Kan, Jie; Li, Jin; Huang, Tongwang; Xiong, Guangming; Hu, Zhong
Abstract: 17β-hydroxysteroid dehydrogenases (17β-HSD) are a group of oxidoreductase enzymes that exhibit high specificity for 17C reduction/oxidation. However, the mechanism of 17β-HSD in oxidizing steroid hormone 17β-estradiol to estrone in bacterium is still unclear. In this work, a functional bacterium Rhodococcus sp. P14 was identified having rapid ability to oxidize estradiol into estrone in mineral salt medium (MSM) within 6 h. The functional genes encoding NADH-dependent oxidoreductase were successfully detected with the help of bioinformatics, and it was identified that it contained two consensus regions affiliated to the short-chain dehydrogenase/reductase (SDR) superfamily. Expression of 17β-HSD could be induced by estradiol in strain P14. The 17β-HSD gene from Rhodococcus sp. P14 was expressed in Escherichia coli strain BL21. Furthermore, recombinant 17β-HSD-expressing BL21 cells showed a high transformation rate, they are capable of transforming estradiol to estrone up to 94%. The purified His-17β-HSD protein also exhibited high catalyzing efficiency. In conclusion, this study provides the first evidence that a novel 17β-HSD in Rhodococcus sp. P14 can catalyze the oxidation of estradiol. Highlights: The bacterium Rhodococcus sp. P14 could efficiently degrade estradiol. The enzyme 17β-HSD from P14 could oxidize of estradiol to estrone. This is the first evidence that 17β-HSD in bacterium oxidizes estradiol.